2013
DOI: 10.5296/emsd.v2i1.3099
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Inner City High Density Liveable? Insight from Residents in Brisbane, Australia

Abstract: Australia's urban form and planning has shifted from traditional individual dwellings on spacious suburban blocks towards higher density urban consolidation. Despite relatively strong market demand for inner city high density (ICHD) living, there is ongoing need to explore and understand the aspects that make this urban form liveable and sustainable. The purpose of this research is to explore the viewpoints of current ICHD residents to better understand the liveability and sustainability matters that affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Another related explanation may be the social aspect of eating out in restaurants, hotels and clubs. Previous studies have found that apartment living may be associated with a lower sense of community (27)(28)(29) and lower social interaction (29)(30)(31)(32) . Households living in apartments may be more likely to go out for meals in restaurants, hotels and clubs to engage in social interaction as the design of their homes and kitchen may not foster social bonds and intimacy among friends and family (32) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another related explanation may be the social aspect of eating out in restaurants, hotels and clubs. Previous studies have found that apartment living may be associated with a lower sense of community (27)(28)(29) and lower social interaction (29)(30)(31)(32) . Households living in apartments may be more likely to go out for meals in restaurants, hotels and clubs to engage in social interaction as the design of their homes and kitchen may not foster social bonds and intimacy among friends and family (32) .…”
Section: Discussionmentioning
confidence: 99%
“…This shift may therefore represent lifestyle changes for many dwellers (26) . Previous research suggests high-rise apartment living is associated with a weaker sense of community (27)(28)(29) , reduced social interaction (29)(30)(31)(32) and more behaviour problems among children (27) . There is limited evidence on the impact of dwelling type on food expenditure and food practices more generally.…”
mentioning
confidence: 99%
“…Australia's urban design has shifted from traditional individual dwellings on spacious suburban blocks to higher density developments with building footprints, parking spaces and concrete driveways covering most (or practically all) of a lot. Such developments have led to significant loss of private greenspace where residents can socialise and children can play; and the loss of amenity and biodiversity (Beumer and Martens 2015;Buys, Vine, and Miller 2013;Hall 2010a). Urban consolidation should not preclude provision of public and private greenspace.…”
Section: Introductionmentioning
confidence: 99%
“…Sanoff and Sawhney (1972) in their study of the town of Asheboro, North Carolina identified dwelling and neighbourhood features as the key factors that contribute to residential environment livability satisfaction of the low-income families housing. The previous researchers posit diverse dimensions but common factors to explore the livability of the living environment namely housing/dwelling unit features (Omuta, 1988;Heylen, 2006;Li, 2012;Namazi-Rad et al, 2012;Buys et al;, physical/neighbourhood conditions (Balsas, 2004;Chaudhury, 2005;Heylen, 2006;Leby and Hashim, 2010;Asiyanbola et al, 2012), economic vitality or development (Balsas, 2004;Song, 2011;Saitluanga, 2013), safety (Leby and Hashim, 2010;Asiyanbola et al, 2012;Lawanson et al, 2013) and social interaction (Pandey et al, 2014a;Leby and Hashim, 2010;Saitluanga, 2013). These dimensions of measuring livability were reported to have high internal reliability index (i.e.…”
Section: Introductionmentioning
confidence: 99%